ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN RUMAH TANGGA PELAKU USAHA DI PARIWISATA PESISIR (DI WILAYAH TANJUNG SETIA DAN LABUHAN JUKUNG, KABUPATEN PESISIR BARAT) - Dike Fransiska; Hari Kaskoyo; Wan Abbas Zakaria (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2020)
Pesisir Barat Regency is one of the regencies located in the coastal regions of Indonesia, precisely in Lampung Province. Pesisir Barat Regency has the main potential in the tourism sector, especially in coastal tourism. Tanjung Setia and LabuhanJukung are tourism which become tourism icons in Pesisir Barat Regency. The purpose of this study is to analyze the allocation and distribution of work of household members, analyze the level of household income and what factors influence it, and determine the level of household welfare in the Tanjung Setia and LabuhanJukung Coastal Areas, Pesisir Barat Regency. The population in this study is household businesses or workers in the Tanjung Setia tourism area and LabuhanJukung. Determination of the number of samples using purposive sampling method. The results of the study revealed that, the allocation of household work time of business operators in the Tanjung Setia tourism area was more dominant in productive activities as well as the LabuhanJukung tourism area. The allocation of productive working time in the Tanjung Setia tourism area is 37.79% or 9.07 hours / day, while in LabuhanJukung is 33, 44% or 8.03 hours / day. The level of household income of business operators in the Tanjung Setia tourism area is relatively greater when compared to LabuhanJukung. In the tourism regions of Tanjung Setia and LabuhanJukung, the level of income is influenced by age, number of family members, distance and location of work time, while the educational variable has no significant effect. The level of household welfare of business operators in the Tanjung Setia tourism area is mostly classified in the welfare category with a percentage of 48, 94% or 48 people, while in LabuhanJukung tourism area is classified as not prosperous with a percentage of 51.97% or 66 people.